Role of interventional radiology in pregnancy complicated by placenta accreta spectrum disorder: systematic review and meta‐analysis. (6th June 2019) - D'Antonio, F.; Iacovelli, A.; Liberati, M.; Leombroni, M.; Murgano, D.; Cali, G.; Khalil, A.; Flacco, M. E.; Scutiero, G.; Iannone, P.; Scambia, G.; Manzoli, L.; et al.
ABSTRACT: Objective: To evaluate the potential benefit of interventional radiology (IR) in improving the outcome of women undergoing surgery for a placenta accreta spectrum (PAS) disorder. Methods: MEDLINE, EMBASE and CINAHL databases were searched for studies comparing outcomes of women with a prenatal diagnosis of PAS who underwent an IR procedure before surgery vs those who did not, using a robust collection of terms relating to PAS. The primary outcome was intraoperative estimated blood loss (EBL). Secondary outcomes were the number of transfused units of packed red blood cells (PRBC), fresh frozen plasma (FFP), platelets and cryoprecipitate, operation time, length of hospital stay, EBL ≥ 2.5 L, PRBC transfused ≥ 5 units, surgical complications, bladder or ureteral injury, relaparotomy, infection, disseminated intravascular coagulation, and complications related to endovascular catheter placement. Only studies reporting on the incidence of, or the mean difference in, the observed outcomes in women affected by a PAS disorder who had vs those who did not have an IR procedure before surgery were considered for inclusion. All outcomes were explored in the overall population of women with a prenatally diagnosed PAS disorder and in those undergoing hysterectomy. Quality assessment of each included study was performed using the Risk Of Bias In Non‐randomized Studies of Interventions (ROBINS‐I) tool. The GRADE methodology was used to assess the quality of the body of retrieved evidence. Results: Fifteen studies (958 women with PAS) were included. In women who underwent IR before surgery, compared with those who did not, mean EBL (mean difference (MD), −1.02 L; 95% CI, −1.60 to −0.43 L; P < 0.001) and the risk of EBL ≥ 2.5 L (odds ratio (OR), 0.18; 95% CI, 0.04–0.78; P = 0.02) were significantly lower. There was no significant difference between the two groups in the other outcomes explored. On subgroup analysis of pregnancies complicated by PAS undergoing hysterectomy, EBL (MD, −0.68 L; 95% CI, −1.24 to −0.12 L; P = 0.02) and the number of transfused FFP units (MD, −1.66; 95% CI, −2.71 to −0.61; P = 0.02) were significantly lower in women who had an endovascular IR procedure compared with controls. Furthermore, women undergoing IR had a significantly lower risk of EBL ≥ 2.5 L (OR, 0.10; 95% CI, 0.02–0.47; P = 0.004). Overall, complications related to the placement of an endovascular catheter occurred in 5.3% (95% CI, 2.6–8.9; I 2, 65.3%) of pregnancies undergoing IR. Overall quality of evidence, as assessed by GRADE, was very low. Conclusions: The current available data provide encouraging evidence that IR procedures may be associated with lower EBL and need for transfusion in pregnancies undergoing surgery for a PAS disorder. However, given the overall very low quality of the evidence, further large studies are needed in order to confirm the beneficial role of IR in improving the outcome of these women. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.